Five-Year Outcomes of Single Trabecular Microbypass Stent (iStent®) Implantation with Phacoemulsification in Korean Patients - Myungjin Kim; Seungsoo Rho; Su-Ho Lim (Ophthalmology and Therapy, 2023)
Abstract Introduction This study reports the long-term intraocular pressure (IOP)-lowering efficacy and safety of a single trabecular microbypass stent (iStent®; Glaukos Corp., San Clemente, CA, USA) for medically controlled open-angle glaucoma in Korean patients. Methods This retrospective observational study included 42 eyes of 35 patients with primary open-angle glaucoma (POAG). All subjects underwent single first-generation iStent® implantation with phacoemulsification by a single surgeon with 5 years follow-up. The primary outcomes were changes in IOP and the number of antiglaucoma medications compared to the preoperative values. The secondary outcome was the proportion of eyes with IOP ≤ 18 mmHg without medication, ≤ 15 mmHg without medication, and ≤ 18 mmHg with or without medication. Adverse events and need for secondary glaucoma surgery were also recorded. Results The mean IOP decreased from 15.8 ± 2.8 to 13.8 ± 1.7 mmHg and the mean number of medications was reduced from 2.24 ± 1.18 to 0.83 ± 1.12, respectively, at year 5. At 3 and 5 years, 80.6% and 78.6% of eyes, respectively, were receiving fewer medications than preoperative numbers. In contrast, only 50% of eyes on four preoperative medications showed medication reductions at 5 years. At years 3 and 5, 61.3% and 53.5% of eyes achieved IOP ≤ 18 mmHg without medication, whereas 90.3% and 89.3% of eyes achieved ≤ 18 mmHg regardless of medication use, respectively. Four eyes required additional glaucoma surgery (two Ahmed glaucoma valve implantations, one trabeculectomy, and one XEN 45 Gel Stent implantation), and all were receiving four preoperative antiglaucoma medications. Transient IOP elevation (14.3%) was the most common complication, followed by five hyphema, one stent obstruction, one stent malposition, and one severe anterior chamber reaction. Conclusion This study demonstrated a good safety profile and sustained IOP reduction after the implantation of a single trabecular microbypass stent (iStent®) with phacoemulsification in Korean patients. The majority of subjects with POAG showed a relatively good response; however, eyes receiving a higher number of medications preoperatively (especially four medications) had difficulty achieving a low target IOP.